Biological Sulfate Reduction in Deep Subseafloor Sediment of Guaymas Basin - Nagakura, Toshiki; Schubert, Florian; Wagner, Dirk; Kallmeyer, Jens, IODP Exp. 385 Shipboard Scientific Party (Frontiers in Microbiology, 2022)
Sulfate reduction is the quantitatively most important process to degrade organic matter in anoxic marine sediment and has been studied intensively in a variety of settings. Guaymas Basin, a young marginal ocean basin, offers the unique opportunity to study sulfate reduction in an environment characterized by organic-rich sediment, high sedimentation rates, and high geothermal gradients (100-958°C km-1). We measured sulfate reduction rates (SRR) in samples taken during the International Ocean Discovery Program (IODP) Expedition 385 using incubation experiments with radiolabeled 35SO42- carried out at in-situ pressure and temperature. The highest SRR (387 nmol cm-3 d-1) was recorded in near-surface sediments from Site U1548C, which had the steepest geothermal gradient (958°C km-1). At this site SRR were generally over an order of magnitude higher than at similar depths at other sites (e.g. 387-157 nmol cm-3 d-1 at 1.9 mbsf from Site U1548C vs 46-1.0 nmol cm-3 d-1 at 2.1 mbsf from Site U1552B). Site U1546D is characterized by a sill intrusion, but it had already reached thermal equilibrium and SRR were in the same range as nearby Site U1545C, which is minimally affected by sills. The wide temperature range observed at each drill site suggests major shifts in microbial community composition with very different temperature optima but awaits confirmation by molecular biological analyses. At the transition between the mesophilic and thermophilic range around 40 to 60°C, sulfate-reducing activity appears to be reduced, particularly in more oligotrophic settings, but shows a slight recovery at higher temperatures.